PsycEXTRA Dataset 1991
DOI: 10.1037/e457182004-001
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of performance-based tests designed to improve naval aviation selection.

Abstract: This report describes the evaluation of a portion of a new aircrew selection test battery recently developed at the Naval Aerospace Medical Research Laboratory. The results indicate that performance-based test measures can be used to predict flight training performance. Several test measures were reliably related to a pass/fail criterion. These results provide support for the prediction of whether or not a candidate will pass or fail training. The results of a hierarchical multiple regression revealed that sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…We were also interested in one CBPT developed by NAMRL (see Blower & Dolgin, 1991). Research has identified that the Psychomotor Test/ Dichotic ListenLig Test (PMT/DLT) is the most powerful if the N.AMRL CBPTs (Delaney, 1992;Street, Chapman, & Helton, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We were also interested in one CBPT developed by NAMRL (see Blower & Dolgin, 1991). Research has identified that the Psychomotor Test/ Dichotic ListenLig Test (PMT/DLT) is the most powerful if the N.AMRL CBPTs (Delaney, 1992;Street, Chapman, & Helton, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…The subtests are arranged in ascending order of difficulty with the final subtest involving coordination of three cursors. A detailed description of the PMT/DLT subtests and variables may be found in Blower and Dolgin (1991) and Shull (1991). The presentation order, administration time, and description of the various components of the PMT/DLT are presented in Table I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this study, the volunteer subjects were also administered NAMRL's Computer Based Performance Test (CBPT) Battery. See Blower and Dolgin [4] for a detailed description of the tests in this battery.…”
Section: The Experimental Datamentioning
confidence: 99%
“…These are usually cases where the job task is similar to the screening task. Other studies suggest that brief (e.g., three to five minute) samples of presumably relevant performance tasks predict job performance modestly (e.g., studies on pilot selection; see Blower and Dolgin, 1991). Thus, the fundamental question of whether one can predict more complex job performance from simple tasks is far from answered.…”
Section: Conceptmentioning
confidence: 99%